2019
DOI: 10.1007/jhep10(2019)241
|View full text |Cite
|
Sign up to set email alerts
|

Weyl fermions in a non-abelian gauge background and trace anomalies

Abstract: We study the trace and chiral anomalies of Weyl fermions in a nonabelian gauge background in four dimensions. Using a Pauli-Villars regularization we identify the trace anomaly, proving that it can be cast in a gauge invariant form, even in the presence of the non-abelian chiral anomaly, that we rederive to check the consistency of our methods. In particular, we find that the trace anomaly does not contain any parity-odd topological contribution, whose presence has been debated in the recent literature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Im(c) 9π 2 F mn F mn + gravitino (21) They are in agreement with [25]. When c is real, it reproduces the results in [32] (with corrections made in [33]).…”
Section: Cp-violating Supersymmetric Weyl Anomalysupporting
confidence: 81%
See 1 more Smart Citation
“…Im(c) 9π 2 F mn F mn + gravitino (21) They are in agreement with [25]. When c is real, it reproduces the results in [32] (with corrections made in [33]).…”
Section: Cp-violating Supersymmetric Weyl Anomalysupporting
confidence: 81%
“…Some time ago, it was suggested that in addition to the Euler density and the Weyl tensor squared, the CP-violating Pontryagin density can appear in the Weyl anomaly [12]. There have been some discussions on the explicit demonstration of the Pontryagin density in the Weyl anomaly in [13][14][15][16][17][18][19][20][21][22][23][24]. In our recent paper [25], we have found that the supersymmetric extension of the CP-violating Weyl anomaly can be consistently formulated.…”
Section: Introductionmentioning
confidence: 91%
“…[4] and [20]. The analogous case of a Weyl fermion in a gauge background has also been studied more recently in [5,12], where it was found that parity-odd terms do not contribute to the trace anomaly in that context as well.…”
Section: Discussionmentioning
confidence: 98%
“…This method has already been applied successfully to several contexts in the past, as the case of two-dimensional b-c systems [10], which bear some analogies to the four-dimensional Weyl fermion case, or the more exotic model of chiral bosons [11]. It is the same method used more recently in [4,5,12] to address the trace anomalies of a Weyl fermion.…”
Section: Introductionmentioning
confidence: 99%
“…However, with strictly four-dimensional regularization methods such as Pauli-Villars regularization [7,8] employed by Bastianelli et al, or Hadamard subtraction used by Zahn and the last author [9], CP-odd terms in the trace anomaly do not arise at all. In between, this has given rise to more general discussions involving gauge anomalies [10,11] and general CP-violating theories [12,13]. Apart from the natural consequences this may have in the building of the Standard Model and extensions thereof, there will also be repercussions in our understanding of the early universe [14][15][16].…”
Section: Introductionmentioning
confidence: 99%